The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-67251-8
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and gait speed rather than lean mass are better indicators for poor cognitive function in older men

Abstract: We aimed to examine muscle strength, function and mass in relation to cognition in older men. this cross-sectional data-set included 292 men aged ≥60 yr. Handgrip strength (kg) was measured by dynamometry, gait speed by 4-metre walk (m/s) and appendicular lean mass (kg) by dual-energy x-ray absorptiometry. cognition was assessed across four domains: psychomotor function, attention, visual learning and working memory. Composite scores for overall cognition were calculated. Bivariate analyses indicated that hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 52 publications
(70 reference statements)
4
29
0
Order By: Relevance
“…Kim et al reported that sarcopenia was associated with cognitive decline only in men in a cross-sectional study [ 25 ]. Furthermore, when specific sarcopenic parameters including muscle mass and physical function (hand grip strength, gait speed) were analyzed separately, low muscle strength and gait speed rather than muscle mass could better predict cognitive impairment in two recent studies [ 26 , 27 ]. Meanwhile, only gait speed, and not hand grip strength or muscle mass, was reported to correlate with cognitive impairment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that sarcopenia was associated with cognitive decline only in men in a cross-sectional study [ 25 ]. Furthermore, when specific sarcopenic parameters including muscle mass and physical function (hand grip strength, gait speed) were analyzed separately, low muscle strength and gait speed rather than muscle mass could better predict cognitive impairment in two recent studies [ 26 , 27 ]. Meanwhile, only gait speed, and not hand grip strength or muscle mass, was reported to correlate with cognitive impairment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence emerging from observational and experimental studies has shown that human body composition and brain function are linked [ 9 , 10 , 13 , 39 , 40 , 41 , 42 , 43 ]. Although sarcopenia and cognitive dysfunction are often considered separate multidimensional concepts, they may have common risk factors and biological pathways.…”
Section: Are Post-stroke Sarcopenia and Cognitive Dysfunction Comomentioning
confidence: 99%
“…Although sarcopenia and cognitive dysfunction are often considered separate multidimensional concepts, they may have common risk factors and biological pathways. In general, advanced age contributes to the decline of skeletal muscle health and cognitive function [ 9 , 10 ]. In older patients in hospital settings, sarcopenia and cognitive dysfunction are strongly associated [ 44 ].…”
Section: Are Post-stroke Sarcopenia and Cognitive Dysfunction Comomentioning
confidence: 99%
See 2 more Smart Citations